A Political Satire for All Times: Reading Hāsyārṇava-prahasanaṁ or the Ocean of Mirth of Jagadēśvara Bhaṭṭāchārya. (June 2019) - Sharma, Jyotirmaya
Hāsyārṇava, the Ocean of Mirth, a medieval Sanskrit political satire, delineates three central themes that require serious consideration. First, the Indic traditions underline the centrality of order in a polity. This preoccupation is underlined by the supremacy of the Rājadharma-daṇḍanīti framework. A great deal of violence and cruelty inheres within this framework. Second, if the order is the site for violence and force, it follows that a glimpse of freedom, unshackled from the conventional implications of the puruṣārthas can only be had in upholding the desirability of disorder. Finally, the Indic traditions can transgress and express dissent with the help of a plurality of philosophical and conceptual alternatives rather than hankering after a single set of foundational values or an inevitable normativity.